2021
DOI: 10.1186/s43014-020-00049-3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential and physicochemical properties of protein hydrolysates from body parts of North Atlantic sea cucumber (Cucumaria frondosa)

Abstract: Protein hydrolysates were prepared from North Atlantic sea cucumber (Cucumaria frondosa) body wall (BW), and processing by-product flower (FL) and internal organs (IN). Sea cucumber proteins from these three tissues were hydrolysed with selected endopeptidases and exopeptidases. The enzymes used were Alcalase (A), and Corolase (C) as endopeptidases and Flavourzyme (F) with both endo- and exopeptidase functions. These were employed individually or in combination under controlled conditions. The hydrolysates so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 74 publications
5
36
0
Order By: Relevance
“…The study found that camelina protein hydrolysate contains peptides that act as electron donors and free radical scavengers to terminate the chain reaction. These findings lend support to the previously reported study on the radical scavenging activities hydrolysates from various plant proteins (He et al, 2013;Hu et al, 2020;Senadheera et al, 2021). According to the authors, hydrolysates produced by alkaline proteases such Alcalase and Flavourzyme have stronger antioxidant activity than those manufactured with other enzymes as Neutrase, papain, bromelain, and pepsin.…”
Section: Dpph Radical Scavenging Activitysupporting
confidence: 89%
See 4 more Smart Citations
“…The study found that camelina protein hydrolysate contains peptides that act as electron donors and free radical scavengers to terminate the chain reaction. These findings lend support to the previously reported study on the radical scavenging activities hydrolysates from various plant proteins (He et al, 2013;Hu et al, 2020;Senadheera et al, 2021). According to the authors, hydrolysates produced by alkaline proteases such Alcalase and Flavourzyme have stronger antioxidant activity than those manufactured with other enzymes as Neutrase, papain, bromelain, and pepsin.…”
Section: Dpph Radical Scavenging Activitysupporting
confidence: 89%
“…Hydrolysis of camelina protein isolates was conducted with Alcalase (0.3 AU/g) and Flavourzyme (50 LAPU/g) under different conditions (Ambigaipalan et al, 2015;Senadheera et al, 2021). The samples were hydrolysed batchwise with Alcalase (AL, pH 8, 50 °C) for 4h, or Flavourzyme (FL, pH 7, 50°C) for 4 h. Enzyme combination treatments were carried out by first hydrolysing with Alcalase for 2h (pH 8, 50 °C), and then adding Flavourzyme for 2h (pH 7, 50°C).…”
Section: Preparation Of Camelina Protein Hydrolysates and Membrane Fractionsmentioning
confidence: 99%
See 3 more Smart Citations